Bank capital structure and the credit channel of central bank asset purchases - Matthieu Darracq Pariès; Grzegorz Hałaj; Christoffer Kok (European Central Bank (ECB), 2016)
With the aim of reigniting inflation in the euro area, in early 2015 the ECB embarked on a large-scale asset purchase programme. We analyse the macroeconomic effects of the Asset Purchase Programme via the banking system, exploiting the cross-section of individual bank portfolio decisions. For this purpose, an augmented version of the DSGE model of Gertler and Karadi (2013), featuring a segmented banking sector, is estimated for the euro area and combined with a bank portfolio optimisation approach using granular bank level data. An important feature of our modelling approach is that it captures the heterogeneity of banks' responses to yield curve shocks, due to individual banks' balance sheet structure, different capital and liquidity constraints as well as different credit and market risk characteristics. The deep parameters of the DSGE model which control the transmission channel of central bank asset purchases are then adjusted to reproduce the easing of lending conditions consistent with the bank-level portfolio optimisation. Our macroeconomic simulations suggest that such unconventional policies have the potential to strongly support the growth momentum in the euro area and significantly lift inflation prospects. The paper also illustrates that the benefits of the measure crucially hinge on banks' ability and incentives to ease their lending conditions, which can vary significantly across jurisdictions and segments of the banking system.
Keywords: C61; E52; G11; 330; banking; DSGE; portfolio optimisation; quantitative easing